Lower Educated Adults Learn Basic Skills Online - Vaske, Ben (LESLLA Symposium Proceedings, 2015)
Using adapted digital exercise material, lower educated adults can work at their own development and towards better participation in society in an informal and non-formal manner. Learners can participate in and be successful in online environments at various levels. Lower educated adults are doing this, independently or with support, through self-motivation and because they want to be at the helm of their own learning process. Digital skills are a precondition for this: they are the new key skills, as opposed to for instance traditional language skills. They provide a springboard to other domains – in addition to literacy and numeracy – such as health, work, parenting and money, which are increasingly digitalised. Digital information channels often put too much focus on language without regard to the users. Digital communication skills are increasingly required, even for lower educated adults. This Dutch contribution shows how important it is for lower educated adults to practise and increase their digital skills on a basic level of literacy, enabling them to perform adequately in digital communication and to operate skillfully in the digital world. This is illustrated using the exercise portal Oefenen.nl (Practise.nl) and the Klik & Tik (Click & Tick) programs that were developed specifically for adults with a low level of education. This offers chances and opportunities for a new style of adult education.